Job Satisfaction of Shop Floor Workers in Automotive Industries in Malaysia - Dawal, S. Z.; Taha, Z.; Ghazilla, R. A. (ANIMA Indonesian Psychological Journal, 2006)
A survey was conducted to investigate the relationship between job satisfaction, job characteristics, environment, job organization and social factors that affect work design in two automotive manufacturing companies in Malaysia. The aim of the study is to determine the factors that influence employees' perception towards their word. One hundred and seventy male subjects between the ages of 18 to 40 years with the mean age of 26.8 and standard deviation (SD) of 5.3 years and mean work experience of 6.5 and SD of 4.9 years were involved. A set of multiple choices questionnaire was developed and data were collected by interviewing the employees at the production plant. The results support the study and showed that job characteristics, environment, job organization and social factors are significantly related to job satisfaction. The potential applications of these results include methods developed in diagnosing the industrial work namely questionnaire design, environment observation and measurements, data collection and statistical analysis to diagnose current industrial work design that affect workers satisfaction. Telah dilakukan sebuah survei untuk meneliti hubungan antara kepuasan kerja, ciri-ciri kerja, lingkungan, organisasi kerja dan faktor-faktor sosial yang mempengaruhi desain kerja pada perusahaan manufaktur otomotif di Malaysia. Tujuan studi ini adalah menentukan faktor-faktor yag mempengaruhi persepsi karyawan terhadap pekerjaannya. Yang terlibat dalam penelitian ini sejumlah 170 subjek laki-laki berusia antara 18 hingga 40 dengan rerata 26.8 tahun dan deviasi baku (SD) 5.3 tahun dan rerata pengalaman kerja 6.5 tahun dan SD 4.9 tahun. Telah dikembangkan seperangkat kuesioner pilihan multipel dan data dikumpulkan melalui wawancara para karyawan di tempat produksi. Hasil-hasilnya mendukung studi dan menunjukkan bahwa ciri-ciri kerja, lingkungan, organisasi kerja dan faktor-faktor sosial terkait secara bermakna dengan kepuasan kerja. Potensi aplikasi hasil-hail ini termasuk metode-metode yang dikembangkan dalam mendiagnosis kerja industrial yaitu desain kuesioner, observasi dan pengukuran lingkungan, koleksi data dan analisi untuk mendiagnosis desain kerja industrial yang mempengaruhi kepuasan para karyawan.